PENGARUH CAMPURAN PUPUK LIMBAH CAIR PABRIK KELAPA SAWIT DENGAN PUPUK NPK MUTIARA TERHADAP KOMPONEN PRODUKSI KACANG HIJAU (Vigna radiata L.) - John Alpiyan Saragih; Husna Yetti; Agus Sutikno (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
The purpose of this research is to determine the effect of mixing LCPKS and NPK and best treatment ofgreen bean production components. This research was conducted in Experimental Field of Agriculture Faculty, University of Riau in October until December 2016. This research uses non factorial Randomized Block Design (RAK) consisting of 5 treatments and 4 replications. The treatments consisted of dosage LCPKS + NPK 0 ml / plot + 60 g / plot, 7.5 ml / plot + 60 g / plot, 15 ml / plot + 45 g / plot, 30 ml / plot + 30 g NPK / Plot, and 45 ml / plot + 15 g NPK. Parameters observed were plant height, flowering age, harvest age, number of pods per plant, number of pods per plant, number of seeds per plant, seed weight per plant, weight of 1000 seeds per plot and seed weight per plot. The data obtained were analyzed using verbal examination and continued with Duncan Multiple Range Test at the 5 % level. The results showed that giving LCPKS + NPK at a dose of 15 ml / plot + 45 g and 30 ml / plot + 30 g NPK showed better results in increasing the components of green bean production.  Keywords: LCPKS and NPK, green beans